Astronomia no ensino de Física: o Radiotelescópio como mediador para o ensino de Ondulatória - Pinto, César Hipólito (2021)
The primary objective was to develop and build a radio telescope for the capturing of specific frequency of 1420 MHz of hydrogen lines and echoes from a meteor shower event and apply it in the process of teaching and learning electromagnetic waves. With that in mind, the theoretical reference used is based on Vygotsky´s Theory for the process of basic concept construction. This choice is justified by the interest in developing important educational standards, not only the teaching of physics, but also building and identification of social-emotional skills of each student: cooperation, persistence, conscientiousness; and relevant, strengthening and improving important technological concepts involved in the particular activity. As an evaluation method, the concept of “culmination” was applied as a reference, and in this context, preliminary results show the key protagonism of students with exciting speeches and interest in new technological activities, once new achievements were accomplished, team members were chosen to participate in the 2020 - 3rd Cube design and INPE's Workshop on Engineering and Space Technologies. The product itself was totally designed and developed with easy to acquire and low-cost materials, making it feasible at any educational reality in the country. Originally, it was applied at a state school in the countryside of the state of São Paulo, sixteen high school students. Finally, it was possible to observe an emotional excitement, which means, the development of autonomy, group work, and technical skills by the students. In the other hand, electromagnetic waves knowledge development led to an improvement in the Physics technical language.